Phenotypic effects of different doses of physical and chemical mutagens in cotton plants - Winkler, Horacio Martín; Cereijo, Antonela Estefania; Scarpin, Gonzalo Joel; Dileo, Pablo Nahuel; Muchut, Robertino Jose; Roeschlin, Roxana Andrea; Lorenzini, Fernando; Paytas, Marcelo Javier; Landau, Alejandra Mabel (Ediciones INTA, 2023)
Induced mutation techniques have been effectively used to obtain new variability in crop plants. Mutations are the primary source of genetic variability and therefore, some control over their frequency can be considered a valuable tool for plant breeding. Mutagens can be grouped into two broad categories according to their nature: physical and chemical. Doses must be optimized to increase the chances of generating mutants and achieve a population of mutagenized plants that allow a successful selection of mutants of interest. The aim of this study was to test the sensitivity of different mutagenic agents on Guazuncho 3 variety cotton seeds. Four doses of each treatment were evaluated and different phenotypic traits were recorded. The greatest effects on germination percentage, germination velocity index, plant survival and somatic effects were observed in treatments with ethyl methanesulfonate (EMS) as the doses increased. Lower but significant effects were recorded in sodium azide (SA) treatments and no significant differences were observed for X-rays and combined treatments (SA+X-rays). The effects on growth rate were significant in chemical treatments with R2 = 0.84 for SA and R2 = 0.97 for EMS. In addition, it was observed that the EMS and X-rays treatments caused a greater number of off-type plants and chlorotic irregular-shaped spots. The results of this preliminary study determined the mutagens doses to be used on Guazuncho 3 cotton seeds, to generate an M1 population for developing a mutation breeding program.